Evaluation of the Life Skills of Students in Adolescence: Scale Development and Analysis - Dilek Erduran Avcı; Fikret Korur (Journal of Science Learning, 2022)
Adolescents have been the leading group for life skills (LS) education in the last decade. The primary purpose of this study was to develop a valid and reliable instrument for assessing the general LS of students in adolescence. In addition, the relation of adolescents' LS to gender, grade level, science/physics course scores, GPA, and socio-economic status variables was examined. This descriptive survey study included two data sets, one for the development of the scale part, including 692 students, and the other for confirmatory analysis and inferential statistics, including 887 students. LS were assessed using the Life Skills Scale (LSS), which consisted of 83 items in 10 sub-dimensions, and evaluated critical thinking, creative thinking, decision making and problem-solving, coping with stress and emotion, social responsibility, teamwork, self-esteem, self-awareness, empathy, and interpersonal relationship and communication skills of the students. The results of the exploratory and confirmatory factor analysis and the reliability coefficient of the scale provided solid statistical evidence, which was coherent with the 10-subdimension model of the scale. The findings revealed that the LSS is a valid and reliable tool for adolescents to evaluate their LS. Students scored highest on empathy, self-awareness, and self-esteem, whereas they scored lowest on teamwork, coping with stress emotion, and critical thinking. There was a significant relationship between various sub-dimensions of LS and some variables such as GPA, grade level, gender, and science/physics course score. The results also indicated that the academically successful students were highly skilled in most LS sub-dimensions.